Projection of runoff characteristics as a response to regional climate change in a Central/Eastern European catchment. Issue 13 (2nd October 2020) - Kis, Anna; Pongrácz, Rita; Bartholy, Judit; Szabó, János Adolf
ABSTRACT: The impact of climate change on runoff characteristics is investigated for the Upper Tisza basin, in eastern Central Europe. For a reliable estimation of uncertainty, an appropriate stochastic weather generator is embedded into a Monte Carlo cycle capable of generating any large number of independent, equally probable, 100-year-long daily sequences of synthetic data with which a hydrological model is driven in order to obtain the hydrological responses to the meteorological data sequences. According to our results, a decrease of daily average runoff is likely to occur in the future in the Upper Tisza basin, especially in July and August. The occurrence of water levels below the critical low level is estimated to increase between July and October. Level-3 flood warnings are projected to be less frequent in the future; however, they will tend to be more severe than in the historical period.